Mitochondria-Related Ferroptosis Drives Cognitive Deficits in Neonatal Mice Following Sevoflurane Administration - Zhang, Piao; Chen, Yeru; Zhang, ShuXia; Chen, Gang (Frontiers in Medicine, 2022)
Multiple sevoflurane exposure may result in cognitive deficits in neonatal animals. This study attempted to investigate the potential mechanism of sevoflurane-induced neurotoxicity in developing hippocampus. Neonatal animals received sevoflurane anesthesia, then the behavioral tests and Golgi-Cox staining were employed to detect the effect of sevoflurane inhalation in adult mice. Then, the mitochondrial function was evaluated by using mito-SOX staining, Fluo calcium indicators, mitochondrial permeability transition pore (mPTP) assay, and JC-1 probe after sevoflurane administration, respectively. Meanwhile, mitochondrial lipid hydroperoxide and ferroptosis were measured by MitoPeDPP and Mito-FerroGreen signals following sevoflurane exposure. Moreover, the ferroptosis and behavioral performance were assessed after deferiprone (DFP) treatment. The results showed that sevoflurane administration induced cognitive impairment accompanied with reducing dendritic length, density and nodes. Additionally, sevoflurane exposure elevated mitochondrial ROS production and cytoplasm calcium levels, triggered the opening of mPTP and decreased the mitochondrial membrane potential (MMP). However, supplement of elamipretide (SS-31) effectively reversed mitochondrial dysfunction. Mitochondrial lipid hydroperoxide production was increased after sevoflurane administration, while Fer-1 treatment reduced lipid hydroperoxide formation. Sevoflurane exposure induced mitochondrial iron overload, while Mito-Tempo treatment reduced iron accumulation. Prussian blue staining showed that the hippocampal iron deposition was apparently increased after sevoflurane inhalation. And the ferroptosis-related proteins expression (including ACSL4, COX2, GPX4 and FTH1) was significantly changed. Whereas, DFP effectively suppressed ferroptosis, and enhanced sevoflurane-induced behavioral malfunction. These findings demonstrated that sevoflurane administration elicited mitochondrial dysfunction and iron dyshomeostasis, and eventually resulted in cognitive impairments, whereas protecting mitochondrial function and chelating neurotoxic iron effectively reversed this pathological processes.